2022
DOI: 10.1021/acsnano.2c02784
|View full text |Cite
|
Sign up to set email alerts
|

Water Flow in Single-Wall Nanotubes: Oxygen Makes It Slip, Hydrogen Makes It Stick

Abstract: Experimental measurements have reported ultrafast and radius-dependent water transport in carbon nanotubes which are absent in boron nitride nanotubes. Despite considerable effort, the origin of this contrasting (and fascinating) behavior is not understood. Here, with the aid of machine learning-based molecular dynamics simulations that deliver first-principles accuracy, we investigate water transport in single-wall carbon and boron nitride nanotubes. Our simulations reveal a large, radius-dependent hydrodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 66 publications
6
49
0
Order By: Relevance
“…This implies that the water molecules experience the same free energy surface at the interface, an example of which is shown in Figure 3b, inset, independent of ω 0 (see the Supporting Information). This confirms that the physical origins of λ THz are not captured by the corrugation of the free energy surface that has been widely used to account for the curvature dependence of friction in CNTs 27,31 and certain differences in hydrodynamic slippage at different materials. 31,33,61,62,67 Instead, the nature of λ THz is entirely dynamical, with the dependence of τ F on ω 0 accounting entirely for the increase in λ THz , as seen in Figure 3c.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…This implies that the water molecules experience the same free energy surface at the interface, an example of which is shown in Figure 3b, inset, independent of ω 0 (see the Supporting Information). This confirms that the physical origins of λ THz are not captured by the corrugation of the free energy surface that has been widely used to account for the curvature dependence of friction in CNTs 27,31 and certain differences in hydrodynamic slippage at different materials. 31,33,61,62,67 Instead, the nature of λ THz is entirely dynamical, with the dependence of τ F on ω 0 accounting entirely for the increase in λ THz , as seen in Figure 3c.…”
supporting
confidence: 56%
“…Of particular curiosity, experiments have found that friction of water on carbon surfaces is ultralow compared to other two-dimensional materials. In addition, the friction of water is much higher on multilayer graphite than monolayer graphene and a peculiar radius dependence in multiwalled carbon nanotubes , is observed. Reproducing these observations has so far remained beyond the realms of molecular simulations, even with highly accurate interatomic potentials . Consequently, these observations cannot be explained by the traditional “surface roughness” approach , that underpins much of our understanding of friction at liquid–solid interfaces.…”
Section: Model Of the Liquid–solid Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, ab initio MD (AIMD) , simulation is able to calculate the atomic forces on the fly and captures bond formation and breakage as naturally taking place in liquid water. Due to the computational cost, there have been only a few studies using AIMD to investigate the microscopic structure and dynamic behavior of water molecules in CNTs. , A recent study has explored water flow in CNTs using a machine learning potential approach, which maintains the accuracy of AIMD and circumvents its high computational cost. However, this study tried to make enough water inside the CNTs so as to approach the bulk water state, different from the system with single-file water inside the CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, advances in microscale/nanoscale technologies and materials have aided the rapid creation of a variety of self-powered microdevices, such as sensors, actuators, and other devices. , As the need for self-powered microgadgets grows, the demand for renewable energy that can be derived from the surrounding environment also increases. To address the energy crisis and meet the need for advanced self-powered microdevices, researchers have explored several novel energy harvesting methods, including thermoelectricity, photovoltaics, electrostatic collectors, jet generators, and piezoelectric. Consequently, without additional external energy input or auxiliary equipment, the conversion of ubiquitous environmental energy into usable energy, such as electricity, is of scientific importance. …”
Section: Introductionmentioning
confidence: 99%